2020
DOI: 10.14744/anatoljcardiol.2020.56346
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated circulating SOCS3 and HP expression associated with stable CAD and acute coronary syndrome: an integrated study based on bioinformatics analysis and case control validation

Abstract: Objective: To extensively use blood transcriptome analysis to identify potential diagnostic and therapeutic targets for cardiovascular diseases. Methods: Two gene expression datasets (GSE59867 and GSE62646) were downloaded from GEO DataSets to identify altered blood transcriptomes in patients with ST-segment elevation myocardial infarction (STEMI) compared to stable coronary artery disease (CAD). Thereafter, several computational approaches were taken to determine funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…They found that compared with healthy controls, patients with stable coronary artery disease (CAD) and acute coronary syndrome (ACS) had significantly lower levels of SOCS3 expression. And the probe expression levels of SOCS3 were significantly upregulated in patients with ST-segment elevation myocardial infarction (STEMI) when compared to stable CAD patients Zhang et al [ 31 ]. Ali et al used ELISA to detect SOCS3 levels in serum.…”
Section: Discussionmentioning
confidence: 99%
“…They found that compared with healthy controls, patients with stable coronary artery disease (CAD) and acute coronary syndrome (ACS) had significantly lower levels of SOCS3 expression. And the probe expression levels of SOCS3 were significantly upregulated in patients with ST-segment elevation myocardial infarction (STEMI) when compared to stable CAD patients Zhang et al [ 31 ]. Ali et al used ELISA to detect SOCS3 levels in serum.…”
Section: Discussionmentioning
confidence: 99%
“…It is better to design study as in the previous literature. They collected peripheral blood samples from 302 patients for a case-control study to further confirm the bioinformatics analysis results based on the GSE59867 and GSE62646 datasets that dysregulated circulating hub genes expression were associated with MI development ( 60 ). Therefore, experiments using in vitro and in vivo models as well as prospective clinical studies will be indispensable for validation of the diagnostic and theragnostic value of these biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The level of haptoglobin significantly reduced in patients with stable coronary artery disease (CHD) and acute coronary syndrome (ACS) compared with healthy controls. Logistic regression analysis showed that a decrease in haptoglobin expression correlates with an increased risk of coronary heart disease [ 6 ]. Patients with acute myocardial infarction (MI) have elevated concentrations of alpha-1-acid glycoprotein [ 7 ].…”
Section: Introductionmentioning
confidence: 99%